2010
DOI: 10.1002/ajmg.a.33377
|View full text |Cite
|
Sign up to set email alerts
|

Consent for genetic research in the Framingham Heart Study

Abstract: Extensive efforts have been aimed at understanding the genetic underpinnings of complex diseases that affect humans. Numerous genome-wide association studies have assessed the association of genes with human disease; including the Framingham Heart Study (FHS), which genotyped 550,000 SNPs in 9,000 participants. The success of such efforts requires high rates of consent by participants, which is dependent on ethical oversight, communications, and trust between research participants and investigators. To study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Our rates of consent to allow us to store and create an immortalized cell line for future research studies, including other health/medical problems like heart disease and diabetes, were comparable to rates found in other community studies adding a genetic arm (Levy et al 2010). Others, too, have found that sharing data and samples with others remains a concern for participants (Trinidad et al 2010).…”
Section: Discussionsupporting
confidence: 71%
“…Our rates of consent to allow us to store and create an immortalized cell line for future research studies, including other health/medical problems like heart disease and diabetes, were comparable to rates found in other community studies adding a genetic arm (Levy et al 2010). Others, too, have found that sharing data and samples with others remains a concern for participants (Trinidad et al 2010).…”
Section: Discussionsupporting
confidence: 71%
“…The acceptance of genetic research for helping children or future generations in respondents from both India and the US may be similar to what is seen with Framingham heart study participants, which is a research project that has continued for generations and has a high rate of acceptance/willingness to participate in genetic research, even to the extent of creation of cell lines for research [31]. A high percentage of study subjects from the third generation (99%) consented to DNA extraction and cell line creation.…”
Section: Discussionmentioning
confidence: 85%
“…This view is shared by others who report good recruitment results after having refined their recruitment practices [3,4,7,8]. Open, frequent and personalized communication with potential participants has been identified as one potential success factor [3,7,8].…”
Section: Potential For Improvementmentioning
confidence: 92%